THE INFLUENCE OF COMPANY SIZE ON THE COMPETITIVENESS OF MEDIUM AND LARGE SCALE MANUFACTURING COMPANIES IN THE CITY OF SERDANG BEDAGAI - Elidawati Elidawati; Azhar Maksum; Idhar Yahya; Nurlinda Nurlinda (Proceedings of the 1st International Conference on Social Science (ICSS), 2024)
As the economy grows and competition intensifies, companies need to understand how their size can affect their ability to compete in the market. Medium and large manufacturing companies have differences in terms of scale of operations, resources, and challenges faced. The purpose of this study is to analyze the effect of company size on the competitiveness of medium and large scale manufacturing companies in Serdang Bedagai City. This research uses quantitative research methods. The data collection techniques in this study were questionnaires and literature studies. The data were then analyzed using the help of the SPSS program, namely validity, reliability and linear regression tests. The results showed that company size affects the competitiveness of medium and large scale manufacturing companies in Serdang Bedagai City. Companies with large size have higher competitiveness than companies with small size